Aproximación semántica a la gramática de "ponerse" y "quedarse"
Our purpose here is to explain the semantic differences between the Spanish pseudo-copular verbs ponerse and quedarse, which both express a change of state. We will distinguish two different constructions with quedarse: 1. with predicates like atónito, de piedra, etc. which express a punctual inchoative event; 2. with predicates like calvo, sin fuerzas, etc. which express a punctual event that delimits the end of a gradual change of state. The verb ponerse denotes a punctual or gradual inchoative event. These aspectual differences lead to different combination properties of these verbs, (i.e., *ponerse/quedarse delgado vs. (ponerse/*quedarse